Innovation in Social Services: A Systematizing Overview based on the EU Research Platform INNOSERV - Langer, Andreas; Eurich, Johannes; Güntner, Simon (Springer eBooks Social Sciences, 2019)
Innovation Actors and Practices -- Innovation and Organisation -- Innovation, Quality and Evaluation.-User Orientation -- Technology and Digitisation -- Context Innovations